Kontribusi minat berwirausaha dan self efficacy terhadap kesiapan berwirausaha di ERA Revolusi Industri 4.0 - Hendrayanti, Silvia; Fauziyanti, Wachidah (JURNAL STIE SEMARANG, 2021)
Abstract. The phenomenon of the low interest and motivation of Indonesian youth for entrepreneurship has become a serious thought for various parties, including the government, the world of education, the industrial world, and the community. Another challenge from the impact of the global information age, the role of humans has been displaced by technology, this is also a problem from the industrial revolution which will fundamentally change the way we work, work and relate to one another. This study aims to examine the contribution of interest in entrepreneurship and self-efficacy to entrepreneurial readiness in the industrial revolution 4.0 era of economics faculty students in Semarang. The population that will be used as research is students of the economics faculty of universities in Semarang who have taken entrepreneurship courses. In this study, the researchers will take 97 samples of respondents from students of the economics faculty of universities in Semarang. In this research, the analytical tool used is Structure Equation Models (SEM) with Partial Least Square (PLS) approach. The results showed that interest in entrepreneurship has a positive and significant effect on entrepreneurial readiness with a coefficient value of 0.309 and a t-value of 4.049. That is, the effect of interest in entrepreneurship on entrepreneurial readiness is 30.9%. Sociological indicators are the indicators that reflect the greatest interest in entrepreneurship. Self efficacy has a positive and significant effect on entrepreneurial readiness with a coefficient value of 0.655 and a t-value of 9.360. That is, the effect of self-efficacy on entrepreneurial readiness is 65.5%. The indicator of being sure to be able to complete tasks that have a wide or narrow (specific) range is the indicator that reflects self-efficacy the most . Abstraksi. Fenomena rendahnya minat dan motivasi pemuda Indonesia untuk berwirausaha menjadi pemikiran serius berbagai pihak, baik pemerintah, dunia pendidikan, dunia industri, maupun masyarakat. Tantangan lain dari dampak era informasi global, peran manusia sudah tergeserkan oleh teknologi, ini merupakan permasalahan juga dari revolusi industri yang secara fundamental akan mengubah cara kerja, bekerja dan berhubungan satu dengan yang lain. Penelitian ini bertujuan untuk menguji kontribusi minat berwirausaha dan self efficacy terhadap kesiapan berwirausaha di era revolusi industri 4.0 mahasiswa fakultas ekonomi di Semarang. Populasi yang akan digunakan sebagai penelitian adalah mahasiswa fakultas ekonomi perguruan tinggi di Semarang yang sudah menempuh matakuliah kewirausahaan.Dalam penelitian ini peneliti akan mengambil 97 sampel responden dari mahasiswa fakultas ekonomi perguruan tinggi di Semarang. Daam penelitian ini alat analisis yang digunakan yaitu Structure Equation Models (SEM) dengan pendekatan Partial Least Square (PLS). Hasil penelitian menunjukkan bahwa minat berwirausaha berpengaruh positif dan signifikan terhadap kesiapan berwirausaha dengan nilai koefisien sebesar 0,309 dan nilai t value sebesar 4,049. Artinya, pengaruh minat berwirausaha terhadap kesiapan berwirausaha sebesar 30,9%. Indikator sociological adalah indikator yang paling besar mencerminkan minat berwirausaha. Self efficacy berpengaruh positif dan signifikan terhadap kesiapan berwirausaha dengan nilai koefisien sebesar 0,655 dan nilai t-value sebesar 9,360. Artinya, pengaruh self efficacy terhadap kesiapan berwirausaha 65,5%. Indikator yakin dapat menyelesaikan tugas yang memiliki range yang luas ataupun sempit (spesifik) adalah indikator yang paling besar mencerminkan self efficacy.